A strong effect of growth medium and organ type on the identification of QTLs for phytate and mineral concentrations in three Arabidopsis thaliana RIL populations - Ghandilyan, Artak (Journal of experimental botany, 2009)
The regulation of mineral accumulation in plants is genetically complex, with several genetic loci involved in the control of one mineral and loci affecting the accumulation of different minerals. To investigate the role of growth medium and organ type on the genetics of mineral accumulation, two existing (LerxKond, LerxAn-1) and one new (LerxEri-1) Arabidopsis thaliana Recombinant Inbred Line populations were raised on soil and hydroponics as substrates. Seeds, roots, and/or rosettes were sampled for the determination of their Ca, Fe, K, Mg, Mn, P or Zn concentrations. For seeds only, the concentration of phytate (IP6), a strong chelator of seed minerals, was determined. Correlations between minerals/IP6, populations, growth conditions, and organs were determined and mineral/IP6 concentration data were used to identify quantitative trait loci (QTLs) for these traits. A striking difference was found between QTLs identified for soil-grown versus hydroponics-grown populations and between QTLs identified for different plant organs. Three common QTLs were identified for several populations, growth conditions, and organs, one of which corresponded to the ERECTA locus, variation of which has a strong effect on plant morphology